Workflow modelling within selected departments of the public administration focused on the regional office (Journal of Information Systems and Technology Management, 2007)
E-government means more likely transformation in nature, affecting the management of human, technological and organisational resources processes. Some authorities state that an integrated process model should make it easy to identify possible ways for improvement. Instruments like Petri-Nets can be suitable for partial solutions in public administration. The main advantages of Petri nets are their graphical notation, their simple semantics, and the rich theory for analyzing.